Specific Aspects of Targeted Training for Weightlifters - Ismailov Mahmud Nodirbek o‘g‘li (Global Scientific Publishing, 2022)
Today, weightlifting is developing in our country, and our athletes are achieving high results at the world level. In this article, some aspects of the organization of training with weightlifting athletes are considered based on the analysis of scientific literature. In addition, the article contains some elements of training planning and the opinions of scientists in this regard. In addition, several recommendations are given regarding developing the athlete's speed and strength qualities and this process.
Keywords: weightlifting; training; physical effort; coach